RUWATAN dalam Masyarakat Jawa - Rukiyah, Rukiyah (Sabda: Jurnal Kajian Kebudayaan, 2008)
Ruwatan is a Javanese traditional ceremony. This paper discusses the basic reason of ruwatan, who should need ruwatan, what elements are present in ruwatan, and how ruwatan ceremonial ordinances. Descriptive analysis answers that ruwatan held as a means to escape from the disaster that purported to be carried in a ruwatan holder. The basis of holding ruwatan is a myth that gave birth Batara Kala who would prey on children of Sukerta.